Sphingolipid degradation in Leishmania (Leishmania) amazonensis. - Agiesh Balakrishna Pillai; Wei Xu; Ou Zhang; Kai Zhang (Public Library of Science (PLoS), 2012)
Human leishmaniasis is caused by more than 20 Leishmania species and has a wide range of symptoms. Our recent studies have demonstrated the essential role of sphingolipid degradation in the virulence of Leishmania (Leishmania) major, a species responsible for localized cutaneous leishmaniasis in the Old World. In this study, we investigated the function of sphingolipid degradation in Leishmania (Leishmania) amazonensis, an etiological agent of localized and diffuse cutaneous leishmaniasis in South America.First, we identified the enzyme LaISCL which is responsible for sphingolipid degradation in L. amazonensis. Primarily localized in the mitochondrion, LaISCL shows increased expression as promastigotes progress from replicative log phase to non-replicative stationary phase. To study its function, null mutants of LaISCL (Laiscl(-)) were generated by targeted gene deletion and complemented through episomal gene add-back. In culture, loss of LaISCL leads to hypersensitivity to acidic pH and poor survival in murine macrophages. In animals, Laiscl(-) mutants exhibit severely attenuated virulence towards C57BL6 mice but are fully infective towards BALB/c mice. This is drastically different from wild type L. amazonensis which cause severe pathology in both BALB/c and C57BL 6 mice.A single enzyme LaISCL is responsible for the turnover of sphingolipids in L. amazonensis. LaISCL exhibits similar expression profile and biochemical property as its ortholog in L. major. Deletion of LaISCL reduces the virulence of L. amazonensis and the outcome of Laiscl(-)-infection is highly dependent on the host's genetic background. Therefore, compared to L. major, the role of sphingolipid degradation in virulence is substantially different in L. amazonensis. Future studies may reveal whether sphingolipid degradation is required for L. amazonensis to cause diffuse cutaneous infections in humans.